Preparation and Properties Evaluation of Chitosan/Alginate Hydrogels in Drug Controlled Release - Zheng, X.F.; Lian, Q. (Asian Journal of Chemistry, 2014)
pH-sensitive hydrogels based on chitosan-sodium alginate was synthesized by using glutaradehyde as cross-link agent. The effects of the degree of the dosage of crosslinking and pH on the swelling behaviours of the hydrogel have been studied and the swelling ratio of this hydrogel in acide solution is much larger than that in alkaline solution. The release behaviour of bovine serum albumin entrapped in the hydrogels was of distinctly difference with the changes of pH value of loading medium. The release of bovine serum albumin in those two kinds of hydrogels in the medium of pH=1 was much quicker in pH=7.4 and 9.18. The amount of bovine serum albumin released from the films at different time intervals was estimated by UV spectrophotomertic method at 279 nm. The dissolution profile and in vitro release kinetics showed that chitosan-sodium alginate hydrogels were promising for controlled delivery of the drug. Formulation containing chitosan and sodium alginate may be suitable as a coating formulation for colon targeted drug delivery.